The Evolution of Indonesian and American Science Education Curriculum: A Comparison Study - Haridza, Risa; Irving, Karen E (EDUCARE, 2017)
ABSTRACT: Curriculum reform is an important strategy to improve the quality of education and human resources in order to increase economic development to better compete in a globalized world. This paper focuses on curriculum development in Indonesia, comparing Indonesian school curriculum to USA (United States of America) school curriculum, and analyzes several factors that strongly influenced Indonesian and American curriculum design and curriculum decision-making. Curriculum development in Indonesia, from independence in 1945 to today, is characterized by cycles of planning and revision. Currently, the goal of the new curriculum requires students to be able to appreciate and implement honesty, discipline, responsibility, compassion (tolerance and working together) and politeness, self-confidence, and effective interactions in social and natural environments. Science curriculum development in the USA schools started with private educational religious institutions. Nowadays, students are encouraged to use scientific information to make choices about issues that arise in everyday life, engage intelligently in public discourse, and debate about important issues that involve science and technology. Several aspects must be taken into account in order to reform the science education curriculum, especially in Indonesia. In designing curriculum, decision makers should involve many parties, such as higher education, researchers, politicians, scientists, teachers, parents, social and religious community leaders, and industrialists. KEY WORDS: Curriculum Development; Science Education; Indonesian and American; Curriculum Design; Curriculum Implementation.Â Â About the Authors: Risa Haridza, M.A. is an Educational Authorities of Pontianak City, Public Middle School 3 Pontianak, Jalan Kalimantan 123, Pontianak 78116, West Borneo, Indonesia. Karen E. Irving, Ph.D. is an Associate Professor at the Department of Teaching and Learning, College of Education and Human Ecology OSU (Ohio State University), 1945 North High St Columbus, Ohio 43210, USA (United States of America). Corresponding author: haridza.1@osu.eduHow to cite this article? Haridza, Risa & Karen E. Irving. (2017). âThe Evolution of Indonesian and American Science Education Curriculum: A Comparison Studyâ in EDUCARE: International Journal for Educational Studies, Vol.9(2), February, pp.95-110. Bandung, Indonesia: Minda Masagi Press owned by ASPENSI, ISSN 1979-7877.Chronicle of the article: Accepted (September 8, 2016); Revised (January 15, 2017); and Published (February 27, 2017).